Religious Culture Learning and Islamic Character Formation in Integrated Islamic Schools - Aceng Kosasih; Amin Haedari; Muhammad Adib Abdushomad; Iman Subasman; Moch. Mahdiyan Nasikhin; Shirin Kulkarni (Jurnal Pendidikan Islam, 2026)
In a global educational context marked by rapid social change, digital transformation, and increasing concerns over moral and character formation, schools are challenged to balance academic excellence with the cultivation of ethical and religious values. This study examines how religious culture learning is planned, implemented, and evaluated in an Islamic junior secondary school, and assesses its contribution to shaping students’ religious character. Employing a qualitative phenomenological design, data were collected through in-depth interviews with school leaders, teachers, students, and parents. The data were analyzed thematically to capture participants’ lived experiences and institutional practices related to religious culture learning. The findings indicate that the school has systematically integrated religious culture into instructional planning, classroom practices, and evaluation processes. Active learning strategies, the use of diverse learning media, and consistent habituation practices were found to effectively support the development of students’ religious character. Nevertheless, the study also identifies challenges arising from contemporary social dynamics and external influences that may affect character formation. The study concludes that religious culture learning, when supported by collaborative engagement with parents and the community, can function as a meaningful pedagogical strategy for character education. These findings imply that Islamic educational institutions need adaptive, context-sensitive models of religious culture learning to ensure continued relevance and effectiveness in fostering holistic student development.